The green value chain construct: instrument validation and green practices among Malaysian corporations. (20th September 2019) - Ong, Jeen Wei; Goh, Guan Gan Gerald; Goh, Choon Yih; Yong, Hui Siang Sally
This study aims to validate the green value chain construct and developed through semi-structured interviews conducted on 35 public listed companies with green focus in Malaysia. Despite the importance of value chain activities as the cornerstone of value creation for businesses, there are only limited research effort that had been directed at empirically validating the green value chain construct. This study validated the green value chain construct through questionnaire surveys among 198 Malaysian corporations. In addition, the adoption of green practices within the value chain among the corporations are examined. The findings suggest that while the corporations are embedding green practices, mainly in the primary value chain activities, the green practices in the secondary value chain activities are however given lower emphasis. The minimal emphasis on embedding green elements in the technology development and human resource management is of concern which raises the question on the sustainability of green practices among these corporations.